2012
DOI: 10.3389/fimmu.2012.00151
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of T Cell Homeostasis and Responses by Pten

Abstract: The generation of lipid products catalyzed by PI3K is critical for normal T cell homeostasis and a productive immune response. PI3K can be activated in response to antigen receptor, co-stimulatory, cytokine, and chemokine signals. Moreover, dysregulation of this pathway frequently occurs in T cell lymphomas and is implicated in lymphoproliferative autoimmune disease. Akt acts as a central mediator of PI3K signals, downstream of which is the mTOR pathway, controlling cell growth and metabolism. Members of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 81 publications
2
31
0
Order By: Relevance
“…Stimulation of the TCR recruits and activates PI3K that modulates the activation of Akt and leads to the downstream inactivation of Forkhead box transcription factor family O (FOXO) transcription factors or mammalian target of rapamycin complex 1 (mTORC1) activation regulating T cell proliferation, growth and glycolytic metabolism (14). The increased proliferation observed in T cells from HG mice could reflect differential regulation in the Akt/mTOR pathway as well.…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation of the TCR recruits and activates PI3K that modulates the activation of Akt and leads to the downstream inactivation of Forkhead box transcription factor family O (FOXO) transcription factors or mammalian target of rapamycin complex 1 (mTORC1) activation regulating T cell proliferation, growth and glycolytic metabolism (14). The increased proliferation observed in T cells from HG mice could reflect differential regulation in the Akt/mTOR pathway as well.…”
Section: Resultsmentioning
confidence: 99%
“…Following the inherited p53 mutation, a Pten mutation is rapidly selected for prior to the development of mature T cells with receptors, which may also explain the decrease in the ratio of productive to nonproductive TCRb sequences (Newton and Turka 2012). While the high mutation frequency in the absence of p53 gives rise to many types of mutations, the loss of Pten metabolically permits the selection of those cells during development in the T-cell lineage (and possibly other lineages) because of its role in the insulin-like growth factor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Mutations in PTEN are associated with multiple cancers in humans, including T-cell malignancies, [6][7][8][9][10][11][12] and targeted deletion of PTEN in murine T cells results in the development of a T-cell malignancy with characteristics of human T-cell acute lymphoblastic leukemia. [13][14][15][16] Interestingly, the most common PTEN-specific mutations that have been detected in primary T-cell acute lymphoblastic leukemia samples are mutational disruptions within the C-terminal region that do not alter phosphatase activity. 7 Moreover, a study reported spontaneous tumor development, including T-cell lymphomas, in mice harboring a knockin mutation that causes loss of the PTEN C-terminal region.…”
Section: Introductionmentioning
confidence: 99%